High-precision gaseous flame temperature field measurement based on quadriwave-lateral shearing interferometry. (March 2023) - Yuan, Xun; Xue, Yuge; Min, Junwei; Yu, Xianghua; Li, Manman; Li, Runze; Yao, Baoli
Highlights: A quadriwave-lateral shearing interferometry is proposed to measure the gaseous flame temperature field. High precision measurement is obtained from a single-shot interferogram. Simple and compact structure allows the system to have a high measurement stability against environmental disturbance. A comprehensive comparison of this method with standard digital holographic interferometry is conducted. Abstract: Quadriwave-lateral shearing interferometry (QLSI) has a broad utilization in quantitative phase imaging (QPI) for refraction-type objects due to its compact structure and stable performance against external disturbance. Here we propose to use the QLSI technique to image and measure the gaseous flame temperature field distribution in high precision. The quantitative phase image of an axisymmetric candle flame is firstly reconstructed from the wire-mesh-like QLSI interferogram, and then the three-dimensional temperature field distribution is calculated with the axisymmetric projection transform algorithm. Compared to the conventional digital holographic interferometry (DHI) based on Mach-Zehnder architecture, the proposed method possesses a high-precision measurement and better stability in disturbed environment, benefiting from the compact common-path structure of QLSI. The temperature measurement errors of the proposed QLSI method are ±5.0 K and ±5.3 K in the presence of airflow disturbance and mechanical vibration, respectively, while those of the DHI method are ±7.6 K and ±12.9 K, respectively.